Male validation factor for three-spined stickleback (Gasterosteus aculeatus) mate choice likely evolutionarily conserved since 50 thousand years. Issue 1 (2nd January 2021) - Gahr, Christoph L.; Boehm, Thomas; Milinski, Manfred
Abstract : During mate choice, three-spined stickleback ( Gasterosteus aculeatus ) females make use of male olfactory cues to determine the suitability of potential mates in a species- and habitat-dependent manner. This signal contains peptides reflecting the individual male's MHC profile and a so-called male validation factor (MVF) indicating the species identity of the sender. In a two-armed flow channel, we exposed gravid females to male odour. The odours from males that produced only the MVF but no MHC signal yet were used to examine whether the MVF of distant stickleback populations, one from Canada and one from Germany – genetically isolated since approximately 31–59 thousand years – has changed to such a degree that present-day females only react to the MVF produced by males from their population of origin. The fish used in the experiments were bred from in vitro-fertilized eggs in either country; those from Canada were shipped for analysis to the Plön laboratory to minimize experimental variability. Given the choice between the two MVFs, females did not significantly prefer the MVF of males of their own origin over the other. However, compared to water, both types of females preferred their own MVF significantly and the foreign MVF almost significantly, respectively, suggesting that they could smell MVFs from both origins. These results suggest that, despite long-term genetic isolation between Canadian and German populations, the three-spined stickleback male validation factor has remained constant and thus represents an evolutionarily conserved signal.